Pengaruh Instagram @Detikcom Terhadap Pemenuhan Kebutuhan Informasi Followers - wicaksana, dwiki agung (Eastasouth Institute, 2023)
This study aims to determine the effect of Instagram @detikcom on fulfilling the information needs of its followers. The concept used is 4 C (Communication, Context, Collaboration, Connection) in the use of social media by Chris Heuerl and information needs from Guha which consists of Catching-up Need Approach, Current Need Approach, Exhaust Need Approach, Everyday Need Approach. Research paradigm namely positivism with a quantitative research approach. The research method was a survey with an explanatory research type. The research population was students of STIKOM Inter Studi Jakarta Class of 2017, totaling 130 people. The sample size was 57 people obtained using the Slovin formula calculation with an error rate of 10%. The sampling technique used is non-probability sampling with a purposive sampling type. The data was collected by distributing questionnaires via the google form link. The data obtained was then processed by statistical calculations using the SPSS variant 25 program. The data was analyzed using the simple linear regression analysis method. The results showed that the social media variable (X) had a fairly strong influence on the fulfillment variable. information needs (Y) on followers. Based on the research results it is known that the R Square value is 0.704 or 70.4%.